Activation of chicken macrophages by isomalto/malto-polysaccharide (IMMP) is facilitated by toll-like receptor 4 (TLR4) - Adil Ijaz; Max Putman; Femke Broere; Victor P.M.G. Rutten; Christine A. Jansen; Edwin J.A. Veldhuizen (Poultry Science)
Isomalto/malto-polysaccharide (IMMP) is a digestion resistant starch that has shown to increase SCFA production in the gut microbiota of human and mice to promote intestinal health. Like other prebiotics, it escapes enzymatic digestion in the small intestine and reaches the colon intact where it can interact with host epithelial and immune cells. Recently it was shown that in vitro IMMP can bind TLR4 on human macrophages resulting in their activation. The purpose of the present study was to investigate putative immune activation effects of IMMP upon direct interaction with chicken macrophages. IMMP stimulation in vitro caused morphological changes in the macrophage cell line HD11 reflected as reduction in cell size and numbers of cytoplasmic projections. Using the extracellular TLR4 blocking agent LPS-RS, it was shown that IMMP stimulation of HD11 cells involved TLR4 signaling. In addition, it activated HD11 cells and monocyte derived macrophages, resulting in the production of nitric oxide and increased phagocytic activity of HD11 cells. In conclusion, our results demonstrate an in vitro effect of IMMP on chicken macrophages which suggests that this carbohydrate compound may have immunomodulatory potential, hence may be used in the future as an alternative strategy to strengthen immune responsiveness to control intestinal infections.